Analysis of Bumrungsuksa office Management Activities in implementing Sharia Business Management in Thailand - Aldira Eka Putri Kaemuddin; Syahrul Amsari (International Conference on Islamic Economic (ICIE), 2026)
This study examines the implementation of Sharia business management within the administrative activities of Bumrungsuksa Islamic Boarding School, located in a predominantly non-Muslim region of Thailand. The research is grounded in the need for effective office management that is simultaneously aligned with Islamic values. The primary objective of this study is to analyze how Sharia principles are applied in managerial processes, including planning, organizing, implementing, and supervising administrative operations. A qualitative descriptive approach was employed, with data collected through observation, interviews, and institutional documentation. The findings reveal that the value of amanah is reflected in the financial management of students’ savings, which are deposited in Sharia-compliant financial institutions to avoid interest-based transactions. Decision-making processes are carried out through regular meetings involving teachers, administrators, and management staff, demonstrating the practice of syura (consultation) in organizational governance. The division of tasks is well-structured, although office administration is still predominantly managed manually, with gradual efforts toward digitalization. Overall, this study indicates that the integration of Sharia-based values in administrative management at Bumrungsuksa has contributed positively to forming an Islamic work culture. Moreover, it holds potential to be developed further as a model for strengthening office management in Islamic educational institutions within minority Muslim contexts.